2022
DOI: 10.1002/cphc.202200581
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Preparation of High‐Quality Perovskite Polycrystalline Films via Crystallization Kinetics Engineering

Abstract: Preparation of lead halide perovskite polycrystalline films at a low annealing temperature is highly restricted by their intrinsically large crystallization activation energy, which hinders the conversion of the precursors/intermediates to perovskites and yields as‐prepared polycrystals with tiny grain sizes and terrible crystal quality. Herein, we demonstrate through in‐situ, real‐time spectroscopic studies that both the nucleation and crystal growth kinetics can be improved without the need for a high anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This conversion process could be then further visualized by in situ optical microscopy observations on top of coated inks 54 and SEM observations of perovskite films at different annealing times/temperatures. 55 It might also be interesting to complement this study with phase field simulations to link nucleation rate, growth rate, and final film morphology and properties (e.g., with various amounts of TU) as studied in previous studies 56,57 to obtain a composition optimized both for the deposition process (faster kinetics in the case of blade-coating) and for the final film quality (high crystallinity and defect-free perovskite).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This conversion process could be then further visualized by in situ optical microscopy observations on top of coated inks 54 and SEM observations of perovskite films at different annealing times/temperatures. 55 It might also be interesting to complement this study with phase field simulations to link nucleation rate, growth rate, and final film morphology and properties (e.g., with various amounts of TU) as studied in previous studies 56,57 to obtain a composition optimized both for the deposition process (faster kinetics in the case of blade-coating) and for the final film quality (high crystallinity and defect-free perovskite).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Sun et al reported the strategy of adding thiourea to the precursor solution to reduce the crystallization activation energy and prepared high-quality perovskite films with an annealing temperature of 50 °C. 21 On the other hand, by selecting the appropriate solvents of the precursor solutions, the solvent evaporation and perovskite nucleation/crystallization can be rationally modulated, thereby forming high-quality perovskite films at low temperature. Consequently, various solvents, such as 2-methoxyethanol, acetonitrile, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), etc., have been explored as precursor solvents for perovskite synthesis without annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preparing perovskite films at relatively low temperatures, even at room temperature, is highly desirable for simplifying production steps and reducing energy consumption. , Recent studies have found that adjusting the precursor solutions by additives can alleviate the adverse effects of annealing and improve the quality of the perovskite films. Sun et al reported the strategy of adding thiourea to the precursor solution to reduce the crystallization activation energy and prepared high-quality perovskite films with an annealing temperature of 50 °C . On the other hand, by selecting the appropriate solvents of the precursor solutions, the solvent evaporation and perovskite nucleation/crystallization can be rationally modulated, thereby forming high-quality perovskite films at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…35 Another strategy is the introduction of ligands to treat interfaces. 36 Thiourea (TU) has been employed as a potent additive or interfacial modifier to increase device performance by defect passivation and crystalline morphology improvement. 43 The sulfhydryl terminal group and the −NH−C group in 3-AP show good coordination with the Pb−I inorganic backbone, inhibiting the formation of I − vacancies in PSCs and coordinating free Pb 2+ to achieve perovskite molecular structure compensation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To tackle the issue mentioned above, many research efforts have been made to the fabrication of high-performance PSC devices, such as additive engineering and interface modification. , Under-coordinated lead ions (Pb 2+ ) and other component ions are identified as the main source of defects in most perovskite materials. , Lewis-base solvents (thiourea, TU) are reported to passivate the trapped states of perovskite (such as Pb 2+ sites) by forming coordinated compounds (such as Pb–S bonds) to strengthen the film quality and stability . Another strategy is the introduction of ligands to treat interfaces . Thiourea (TU) has been employed as a potent additive or interfacial modifier to increase device performance by defect passivation and crystalline morphology improvement. Wang et al added TU as a Lewis base into the CH 3 NH 3 PbI 3 precursor solution to interact with PbI 2 in the perovskite film, slowing down the interaction of MAI and PbI 2 for enlargement of perovskite grain size .…”
Section: Introductionmentioning
confidence: 99%